Motivation, Regulation And Actor Constellations - Experiences From A Multidisciplinary Research Project On Health And Wellbeing As Part Of The Internet Of Things - Andrés Laya; Mårten Sundquist; Jan Markendahl (International Telecommunications Society (ITS), 2015)
Internet of Things is an inherently multi-disciplinary area, as mobile connectivity, sensor device technologies and cloud solutions make strong impact in a multitude of applications in diverse sectors. In this paper we study some technical solutions, business models and behavior aspects of IoT in a Health and Wellbeing context. The work is based on an ongoing research project initiated by a wireless research center. This project includes two startup-up companies that are developing services based on connected devices. As part of the evaluation activities, the project counts with the collaboration of the largest nonprofit training organization in Sweden. As part of the research project, a prototype application is developed for training. Leveraging on the insights related to the individual motivational aspects, collected from an end-user study on motivational and adoptability aspects of Internet of Things in a workout context. In order to better understand the context on which services are provided, an ecosystem analysis is elaborated in order to highlight the differences between the healthcare and wellbeing contexts.
Keywords: 330